EVALUATION OF FOREIGN INVESTMENT USE IN OIL AND GAS COMPLEX OF KAZAKHSTAN - Gulsara Dzholdasbayeva; Gulimai Amaniyazova (European Scientific Journal, ESJ, 2014)
In modern conditions of oil and gas functioning there is exigency in search of field reserves of development at the expense of rational use of investment resources and efficient realization of investment projects. In the present situation such tasks solution is possible only in the framework of strategy development of component parts of the complex, including efficient attraction of foreign investment and mechanisms formation of its use.